Nodulation of soybean under no-tillage in comparison to conventional tillage - Voss, Marcio; Sidiras, Nikolaos (Pesquisa Agropecuaria Brasileira, 2014)
Nodulation of soybeans was studied at two sites on a Dusky Latosol dystrophic at Londrina, alter six years of no-tillage and conventional tillage in soybean (Glycine max (L.) Merrill)-wheat-soybean, maize (Zea mays)-wheat-soybean and cotton (Gossypium hirsutum (L.)-wheat-soybean rotations and after seven years in a soybean-wheat-soybean rotation, respectively. The same evaluation was carried out on a Dark-Red Latosol, at Carambeí, after two years of no-tillage and conventional tillage, in a lupine-maize-triticale-soybean rotation. Better nodulation was found under no-tillage than conventional tillage, dry weight of nodules being 2, 5 times higher. The differences were less market in the soybean-wheat-soybean rotation at Londrina. Also, the distribution of nodules in 10 cm of depth intervals of the soil profile where studied for a Dusky Latosol dystrophic after four years of conventional or no-tillage. In no-tillage, 69% of the nodules were found in 0-20 cm of depth, the rest being distributed down to a depth of 60 cm. In conventional tillage, 85% of the nodules were found in the first 20 cm and the rest until a depth of 40-50 cm. Possible reasons for the better nodulation under no tillage are discussed. The results obtained indicate a higher stability of biological nitrogen fixation under no-tillage than conventional tillage.